Benthic metabolism on Chatham Rise, New Zealand continental margin: Temporal and spatial variability, and relationships with macrofauna and environmental factors. (May 2020) - Leduc, Daniel; Nodder, Scott D.; Pinkerton, Matt; Pilditch, Conrad A.
Abstract: Predicting the impacts of anthropogenic disturbance on deep-sea ecosystems requires a thorough understanding of both environmental and faunal drivers of ecosystem function. Studies of deep-sea ecosystems, however, typically consider environmental drivers only and seldom investigate the effects of seabed communities on ecosystem processes. Here, we describe spatial and temporal variation in sediment community oxygen consumption (SCOC), a measure of benthic metabolism and carbon mineralisation, across several sites on Chatham Rise, off the east coast off New Zealand's South Island, and investigate relationships between environmental factors, macrofauna community parameters, and SCOC in order to quantify their relative contributions to benthic metabolism. SCOC differed significantly among sites but not between the two sampling events in August and December 2015. SCOC was significantly and most strongly correlated with estimated particulate organic carbon flux in both August and December in marginal regressions (R 2  = 0.53–0.61), followed by macrofaunal abundance (0.28–0.52), macrofaunal taxon richness (0.09–0.50) and water depth (0.30–0.35). Variation partitioning analysis showed that in late winter (August), most of the variability in SCOC was accounted for by environmental variables independently of macrofauna, whereas in summer (December), most of the variability in SCOC was accounted for by the combined effects of environment and macrofauna. We also observed a greater effect of macrofauna independent of environment in summer than in late winter (R 2  = 0.13 and 0.05, respectively). Our findings indicate that the contribution of macrofauna to benthic metabolism can be substantial and vary temporally. In addition, our findings suggest that the shifts in ecosystem function resulting from anthropogenic stressors will be difficult to predict due to the interactive effects of environment and macrofauna on benthic metabolism. Nevertheless, if particulate organic carbon flux decreases on Chatham Rise as predicted in climate change scenarios, we anticipate that impacts on benthic metabolism will be most strongly felt in the less productive areas of the rise due to the stronger link between macrofauna and SCOC at low macrofaunal densities. Highlights: Benthic metabolism varied among sites but not sampling events. POC flux and macrofauna abundance were main drivers of metabolism. Stronger correlation between macrofauna and metabolism at low macrofauna densities. Metabolism also driven by interaction of environmental and macrofaunal factors. Future change in ecosystem function difficult to predict due to this interaction.